Temporal variability of particle flux and its components in the Gotland Basin, eastern Baltic Sea - Beltran-Perez, Oscar Dario; Voss, Maren; Pollehne, Falk; Liskow, Iris; Waniek, Joanna Jadwiga (Frontiers in Earth Science, 2023)
Sinking particles were studied by analyzing samples collected in a sediment trap at 180 m depth in the Gotland Basin, eastern Baltic Sea between 1999 and 2020. The aim of this study was to determine the temporal variability of the particle flux and its components and how their changes are linked to phytoplankton blooms. The variables studied included total particle flux, particulate organic carbon and nitrogen, biogenic silica, C:N ratio and the isotopic composition of organic carbon and nitrogen. The total particle flux and its components reached maximum values in 2003, 2012 and 2015. Long-term means over the 22-year period of the total particle flux and its components particulate organic carbon and nitrogen, biogenic silica were estimated at around 152, 22, 3 and 8 mg m−2 d−1, respectively. The C:N ratio and the isotopic composition of organic carbon and nitrogen showed high variability around their long-term means of 9, -25‰ and 4‰, respectively. The annual variability of the components of the flux particulate organic carbon (3–65 mg m−2 d−1), particulate organic nitrogen (0.4–9 mg m−2 d−1) and biogenic silica (1–24 mg m−2 d−1) exhibited the same general pattern as the total particle flux (11–450 mg m−2 d−1) over the study period. On the seasonal scale, sinking material in summer contributed roughly one-third (31%) to the total particle flux, followed by winter (27%), spring (24%) and autumn (19%). The highest particle flux occurred mostly in April, July and November, during and after the appearance of phytoplankton blooms in the Gotland Basin. The phytoplankton community changed from silicon-rich species to nitrogen-fixing cyanobacteria, indicating a shift in nitrogen sources from nitrate-based to N2-based over the year. The spring bloom, dominated by diatoms, was characterized by a lighter carbon and heavier nitrogen isotopic composition, while the summer bloom, mainly of diazotrophic cyanobacteria, was characterized in contrary by heavier carbon and lighter nitrogen isotopes. Although no trend was found in the data, the variability observed in the sinking material was related to the changes over time in the phytoplankton community in the Gotland Basin. The findings of this study provide new and valuable information for our understanding of the temporal variability of sinking material linked to the development of phytoplankton blooms and nutrient sources in the Gotland Basin, and underscore the importance of continued monitoring to understand the potential impacts of environmental changes on this fragile ecosystem.